Bone marrow aspiration in haematological disorders: study at a tertiary care centre - Khan, Subuh Parvez; Geelani, Sajad; Akhter, Shareefa; Bhat, Shuaeb; Hussain, Saleem; Manzoor, Fahim; Rasool, Javid; Khan, Fiza Parvez (International Journal of Research in Medical Sciences, 2018)
Background: The bone marrow examination is an essential investigation for the diagnosis and management of many disorders of the blood and bone marrow. Bone marrow aspiration (BMA) alone is usually sufficient to diagnose nutritional anaemias, and most of the acute leukaemias. Aim was to study the spectrum of haematological disorders diagnosed on bone marrow aspiration. Methods: This study was conducted in the Department of Clinical Haematology in Sher e Kashmir Institute of Medical Sciences, Kashmir for a period of 2 years from December 2015 to December 2017. Bone marrow examination of 2131 cases of suspected hematological disorders was carried out. Bone marrow was aspirated from posterior superior iliac spine under local anaesthesia. Aspirates of dry tap were excluded from the study. Aspiration smears where stained with Leishmann stain for morphological examination. Results: A total of 2131 cases were included in this study. Male to female ratio in our study was 1.9:1. The age range of cases was from 1-80 years and the mean age was 47.3 years. Anemia was the most common haematological disorder in our study accounting for 25.6% of cases followed by acute leukaemia accounting for 22.3% and multiple myeloma (13.3%). Among anemias, megaloblastic anemia was most common followed by dual deficieny anemia. Among leukaemias, acute myeloid leukaemia (13.2%) was more common than acute lymphoblastic leukaemia (9.1%). Conclusions: Bone marrow aspiration cytology is a mildly invasive technique which can diagnose many hematological and non-hematologic diseases that can be confirmed by more advanced investigations viz. serological, biochemical or molecular. It is a highly informative test procedure performed for evaluating blood and blood related diseases in our environment.